Effects of diabetes mellitus on dental pulp: A systematic review of in vivo and in vitro studies - Pimenta, Rafaella Milla Nunes; dos Reis-Prado, Alexandre Henrique; de Castro Oliveira, Sabrina; Goto, Juliana [UNESP]; Cosme-Silva, Leopoldo; Cintra, Luciano Tavares Angelo [UNESP]; Benetti, Francine (Wiley, 2022)
Objectives: This systematic review (PROSPERO CRD42021227711) evaluated the influence of diabetes mellitus (DM) on the response of the pulp tissue and in the pulp cells behaviour. Materials and Methods: Searches in PubMed/MEDLINE, Embase, Web of Science and OpenGrey were performed until March 2022. Studies evaluating the effects of DM in the pulp tissue inflammation and in the cell behaviour were included, followed by risk of bias assessment (Methodological Index for Non-Randomized Studies and SYRCLE's RoB tools). The meta-analysis was unfeasible, and a narrative synthesis for each outcome was provided. Results: Of the 615 studies, 21 were eligible, mainly with in vivo analysis (16 studies). The pulp inflammation (10 studies) was analysed mainly by haematoxylin–eosin stain; DM increased pulp inflammation/degeneration in 9 studies, especially after dental procedures. The cell viability (5 studies) was analysed mostly using MTT assay; DM and glycating agents decreased cellular viability in 3 studies. DM reduced collagen in all of three studies. There were controversial results regarding mineralization; however, increased alkaline phosphatase was reported in three of four studies. Conclusions: DM seems to increase inflammation/degeneration and mineralization in the pulp tissue while reducing cell proliferation. Further analyses in human pulp are important to provide stronger evidence.
Keywords: diabetes mellitus; hyperglycaemia; inflammation; insulin resistance; pulp tissue; systematic review